ANALYSIS OF FACTORS AFFECTING CAPITAL EXPENDITURE IN THE PROVINCE OF YOGYAKARTA IN 2013-2022 - Suhesti Ningsih; Hafizah Wa Akromah; Muh Hasan Ma'ruf (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study was to examine the effect of local taxes, regional levies, general allocation funds, and special allocation funds on capital expenditures. This study uses data on the realization of the local government budget (APBD) for 2013 to 2022 taken from the Ministry of Finance's Directorate General of Fiscal Balance (DJPK) website. The population in this study are all regencies and cities in Yogyakarta. The sampling technique used was Saturated Sample with a total sample of 5 regions consisting of 4 districts and 1 city. This type of research is quantitative research using descriptive statistical tests, classical assumption tests, determination tests (R2), statistical tests F tests and t tests tested using SPSS version 26. The results of this study indicate that: 1) local taxes affect capital expenditure; 2) regional levies have no effect on capital expenditures; 3) general allocation funds affect capital expenditure; 4) special allocation funds have an impact on capital expenditures.Whit an adjust R2value of 0,664 meaning 66,4% of the dependent variable.